Upaya Sekolah Dalam Membentuk Sikaptawadhu Siswa Kepada Guru di MTS 3 Ponorogo Tahun Ajaran 2021-2022 - Aulia, Mohamad Faisal; Haryati, Dini (ANTHOR: Education and Learning Journal, 2023)
This study aims to determine the school's efforts in forming students' attitudes of humility towards teachers at MTs 3 Ponorogo. The method in this study uses a qualitative descriptive research type. The data in this study were in the form of systematic observations and recordings of the symptoms that appeared in the research object, as well as interviews with teachers at MTs 03 Ponorogo. The results of the discussion in this study indicate that forming a humble attitude of students through habituation activities and giving advice includes; First, by exemplary, what is meant is what has been exemplified by the teacher when the teachers are humble towards the school principal as the leader of the institution and piety in worship and piety to Allah SWT. Second Habituation, through handshake habituation activities, students are taught to be istiqomah and get used to shaking hands so that they always humble themselves to their teachers who have given them knowledge. Third, Advice, with the method of giving advice conveyed by the head of the madrasa in morning cult activities, so that it is increasingly embedded in the hearts and souls of students to always be humble towards the teacher.